(3JGQjN GdHQjgis
(3ChdgG (B:s
(3eHJhQ GdChd hChd GdehLhO efg (B: (3JQLeI GdSjO GdTQja YR GdOjf eMeO Hf EHQGgje Hf Ydi GdeQJVi GdgGOhi GdMSfi s
(3BNQgG (B:s
(3jfJgi HJQLeI Gdabjg HQgGf GdOjf EHQGgje Hf CMeO Hf EHQGgje GdYSbdGfi hGdEeGe CHj ESMGb EHQGgje Hf fXGe Hf efUhQ GdTjQGRi hBNQ eG ajg (B: (3GdHhd jJYOi eMdg HQWhHJg ajfLS ZjQg , ceG Cf GdfejeI JJYOi ef TNU Edi TNU Edi TNU s
(3HgG fXGe GdJYbjHIs
(3ai JQGLe Gdjefjjfs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdJGQjNs